Pelaksanaan Kegiatan Ekstrakurikuler Kursus Kader Dakwah (KKD) dalam Meningkatkan Minat Siswa di MAN 2 Model Medan - Neliwati Neliwati; Adinda Putri Aulia; Jihan Emelia Sari; Zakiyah Khairani Pasaribu (Tarbiatuna: Journal of Islamic Education Studies, 2024)
KKD activities are very important to develop in schools because they can improve their learning experience and help them discover their interests in the religious field. The method in this research is qualitative field. The aim of this research is to describe and analyze KKD extracurriculars in increasing student interest in MAN 2 Model Medan. Adapun metode dalam penelitian ini ialah penelitian kualitatif lapangan yang berlokasi di MAN 2 Model Medan. The results obtained in this research are: 1) The implementation of the KKD extracurricular program in increasing student interest in MAN 2 Medan Model is that the implementation of the KKD extracurricular program is realized by carrying out activities that develop students' religious understanding, communication skills and leadership qualities. 2) The contribution of the KKD extracurricular program in increasing student interest at MAN 2 Model Medan is that it provides opportunities to develop preaching, leadership and social skills, which can increase student interest.